Emerging role of MRI in breast cancer screening, pitfalls of current breast screening in Thailand. - Wongkietkachorn, A.; Tantiphlachiva , K. (Chulalongkorn Medical Journal, 2023)
Breast cancer is the most common cancer among women worldwide. An advance in breast cancer screening can decrease its fatality rate. However, there are screening problems in Thailand. Current tools used for breast cancer risk assessment, most of them are based on database from the Caucasian are not applicable for Asian people. Mammogram also has limitations as used for the Thais. Breast MRI can alleviate these limitations. However, it is expensive and could produce a lot of false positive results. Thus, there should be clear guidelines for breast MRI for the Thais to solve the current problem.